Spontaneous Subdural Haematoma Developing Secondary to Arachnoid Cyst Rupture - Mehmet Onur Yüksel (Journal of Clinical and Diagnostic Research, 2016)
Arachnoid cysts are congenital, benign, non-neoplastic, extra-axial intra-arachnoidal lesions. Arachnoid cysts rarely become symptomatic, with bleeding. Intracranial haemorrhage as a complication of arachnoid cyst is a very rare condition. It is well-known that mid-cranial fossa cysts might cause intracerebral haemorrhage or subdural haematoma secondary to traumas. However, the occurrence of spontaneous subdural haematoma secondary to arachnoid cysts, developing without any trauma, is even rarer. A 17-year-old boy presenting with diplopia and headache, with no history of trauma, was diagnosed with left temporal lobe arachnoid cyst and left fronto-parietal subdural haematoma. He was operated on, solely for his haematoma, with no intervention performed for the arachnoid cyst. Authors suggest that it is sufficient to perform an operation for the haematoma only -without arachnoid cyst resection- if there is no clinical presentation specific to the arachnoid cyst itself.